The Characterisation of Thrombus Development in an Improved Model of Arterio-Venous Shunt Thrombosis in the Rat and the Effects of Recombinant Desulphatohirudin (CGP 39393), Heparin, and lloprost - Peters, R F; Lees, C M; Mitchell, K A; Tweed, M F; Talbot, M D; Wallis, R B (Thrombosis and Haemostasis, 1991)
An existing arterio-venous shunt thrombosis model in the rat has been modified to increase its usefulness for the testing of antithrombotic agents and characterised using morphological and radiometric techniques. The thrombus formed on the cotton thread held in the shunt was found to be composed of platelet aggregates surrounded by red thrombus. After 30 min of blood flow there was a 15-fold increase in the platelet content of the thrombus and a 4-fold increase in the fibrin(ogen) content compared with an equivalent weight of whole blood.Use of the anticoagulants recombinant desulphatohirudin (CGP 39393, 4 mg/kg, s.c.) and unfractionated heparin (800 IU/ kg, s.c.) showed that approx. 90% inhibition of thrombus weight and approx. 80% inhibition of fibrin(ogen) content could be achieved without significant effect on the platelet content. Conversely, using the platelet inhibitor lloprost (1 Μg kg−1 min−1), a reduction in thrombus weight of 50% was associated with 75% inhibition of platelet content and only 20% inhibition of fibrinogen). These observations suggest that the growth of this type of thrombus is largely the result of continued fibrin formation rather than continued platelet recruitment and activation.